The The Influence of Will-Skill-Tool (WST) on Technology Integration of Prospective Teachers - Leny Noviani; Andini Nur Rachmawati; Leny Kurnia Oktaviani (Universitas Pendidikan Ganesha, 2025)
The rapid development of technology and science requires teachers to possess the ability to integrate Information and Communication Technology (ICT) into the learning process to enhance its quality, effectiveness, and relevance. However, the readiness and capability of pre-service teachers in utilizing technology remain relatively low. Based on the Will-Skill-Tool (WST) model, this study aims to analyze the influence of attitudes toward ICT use, self-efficacy, digital competence, and the use of digital devices on technology integration among pre-service teachers, as well as to examine gender-based differences. This quantitative study involved pre-service teachers from various study programs selected through proportional random sampling. Data were collected using an online questionnaire that had been tested for validity and reliability. Data analysis was conducted using hierarchical regression, partial tests, determination coefficient tests, and non-parametric analysis. The results indicate that attitudes toward ICT, self-efficacy, digital competence, and the use of digital devices have a positive and significant effect on technology integration. No significant differences were found between male and female pre-service teachers across all variables. These findings highlight the importance of strengthening positive attitudes, self-efficacy, and digital literacy competencies in teacher education curricula to support technology-based learning transformation.